Enhancing sustainable livestock support through Kaliwo agroforestry in Southwest Sumba District, Indonesia - WILHELMUS YAPE KII; AKHMAD SODIQ; JUNI SUMARMONO; NOVIE ANDRI SETIANTO; ZAINAL A. JELAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kii WY, Sodiq A, Sumarmono J, Setianto NA, Jelan ZA. 2025. Enhancing sustainable livestock support through Kaliwo agroforestry in Southwest Sumba District, Indonesia. Biodiversitas 26: 73-84. The agroforestry system is one of the most popular land management systems related to livestock production. The objectives of this study were to establish the roles of Kaliwo agroforestry and its interconnections with the livestock production system as a source of animal feed, a free-range habitat for poultry such as chickens and ducks, and sources of local materials for the construction of livestock enclosures within the Southwest Sumba District, Indonesia. The research used a qualitative descriptive method involving 420 farmers. We collected data using questionnaires, Focus Group Discussions (FGDs), and direct observation in three agro-ecosystem zones: lowland (Loura and Kodi) and highland (Wewewa). The triangulation method validated the data obtained from interviews, observations, and FGDs. We performed the descriptive analysis using both statistical and non-statistical methods. The findings indicated that farmers procured 18 species of forage from Kaliwo as feed for both ruminants (goats, buffaloes, and cattle) and non-ruminants (pigs and horses), particularly during the dry season when forage in pastures was scarce. Furthermore, Kaliwo serves as a free-range environment for poultry and livestock, including pigs and goats in Loura, and it constitutes the main source of materials for the construction of livestock pens. Farmers repurpose residual fodder and manure as organic fertilizer for a variety of crops cultivated in Kaliwo and small farms. Kaliwo is considered one of the key resources in livestock production systems for its long establishment and favourable adaptation to the natural environment. The integration of agroforestry practices with livestock husbandry can serve as a paradigm for sustainable livestock farming by leveraging local ecological wisdom.